Construct Validity and Reliability of a New Spanish Empathy Questionnaire for Children and Early Adolescents - Richaud, Maria C.; Lemos, Viviana N.; Mesurado, Belen; Oros, Laura (Frontiers in Psychology, 2017)
Abstract Empathy is a basic socio-emotional process of human development that involves the ability to perceive, share, and understand the emotional states of others. This process is essential to successful social functioning. However, despite its significance, empathy has been difficult to define and measure, particularly when incorporating both its emotional and cognitive aspects. The purpose of this study was to develop an Empathy Questionnaire for children aged 9 to 12 years based on a model of social cognitive neuroscience and to analyze its construct validity and reliability. This questionnaire aimed to integrate the following aspects: emotional contagion, self-other awareness, perspective-taking, emotional regulation, and empathic action. Three studies were conducted. Study 1 evaluated the discriminative power of the items and studied the underlying structure of the instrument using exploratory factor analysis. In Study 2, confirmatory factor analysis was performed to test the model obtained. Finally, the goal of Study 3 was to analyze the convergent and discriminant validity of the questionnaire and the internal consistency of its dimensions. The final version of the instrument contained 15 items that operationalized the previously listed dimensions. The results of the 3 studies indicated that the questionnaire had good validity and reliability. This study has important implications for research and clinical practice. Given its simplicity and brevity, this new self-report scale may work well as a screening method to evaluate the key psychological issues underlying numerous child behaviors that predict the success or failure of social relationships, individual quality of life, and mental well-being. Key words: multidimensional empathy, new questionnaire, evaluation, psychometrics, validity, childhood